The effects of thinking styles and inventive problem-solving on the problem-solving skills for design and technology students - Charanjit Kaur Swaran Singh (Tanjung Malim, 2023)
The effects of thinking styles and inventive problem-solving on the problem-solving skills for design and technology students by Charanjit Kaur Swaran Singh